Natural history and symptomatology of Helicobacter pylori in childhood and factors determining the epidemiology of infection - ÖZEN, AHMET OĞUZHAN; ERTEM ŞAHİNOĞLU, DENİZ (My University, 2006)
Background: High seroprevalence rates for Helicobacter pylori have been reported in developing countries, yet few studies exist determining the pattern of change in the epidemiology of H. pylori infection in children. The knowledge of acquisition and loss rates of H. pylori and the relevance to the sociodemographic properties and the symptomatology of infection may provide clues for lifestyle changes that might protect children from infection, and also, it may provide rationale for eradication, screening, and protection policies. Our aim was to conduct a prospective study to elucidate the outcome, rate of acquisition, and loss of H. pylori infection in a population of healthy children. Methods: This study is based on follow-up of 327 healthy Turkish children aged 3 to 12 years. The follow-up was conducted 6 years after the baseline examination. Helicobacter pylori status was determined by 13C-urea breath test. Children were investigated for sociodemographic variables and several symptoms. Results: Data from 136 (41%) of 327 children were available. The prevalence of infection increased from 52.9% to 56.6%, mainly increasing in children younger than 10 years. The incidence of H. pylori infection among previously uninfected children was 14%, and the loss rate of infection among previously infected children was 5.5% during the follow-up. Socioeconomic status, household density, and antibiotic use during last 6 months were inversely related to H. pylori prevalence. Children infected with H. pylori were complaining more often of headache but not of abdominal pain or dyspepsia. Conclusions: In this study, the acquisition rate of H. pylori infection was 2.5-fold higher than the loss of infection, and the acquisition mostly occurred before 10 years of age. Data regarding acquisition and loss of H. pylori infection are critical for understanding the epidemiology of infection and development of preventive and treatment strategies. © 2006 by Lippincott Williams & Wilkins.
Keywords: 13C-urea breath test; Children; Epidemiology; Follow-up; H. pylori